2013
DOI: 10.1021/jf3048753
|View full text |Cite
|
Sign up to set email alerts
|

New Precursor of 3-Mercaptohexan-1-ol in Grape Juice: Thiol-Forming Potential and Kinetics during Early Stages of Must Fermentation

Abstract: Two volatile thiols, 3-mercaptohexan-1-ol (3MH) and 3-mercaptohexyl acetate (3MHA), are key aroma impact compounds in many young white wines, especially of the variety Sauvignon blanc (SB). Although great effort has been invested to identify their precursors in recent years, the origin of the majority of 3MH and 3MHA generated during wine fermentation still cannot be explained. Here we demonstrate that supplying an external source of hydrogen sulfide to grape juice hugely increases its thiol-forming potential.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 57 publications
2
51
0
Order By: Relevance
“…Harsch et al (2013) identified (E)-2-hexenal and its corresponding alcohol, (E)-2-hexen-1-ol, as precursors to the formation of 3MH (Harsch et al 2013). This work established the potential for enhancing 3MH and 3MHA in the presence of a sulfur donor and (E)-2-hexenal and (E)-2-hexen-1-ol, opening the door to the possibility of using yeast to enhance production of positive aroma thiols (Figure 3) (Harsch et al 2013).…”
Section: Regulation Of Secondary Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Harsch et al (2013) identified (E)-2-hexenal and its corresponding alcohol, (E)-2-hexen-1-ol, as precursors to the formation of 3MH (Harsch et al 2013). This work established the potential for enhancing 3MH and 3MHA in the presence of a sulfur donor and (E)-2-hexenal and (E)-2-hexen-1-ol, opening the door to the possibility of using yeast to enhance production of positive aroma thiols (Figure 3) (Harsch et al 2013).…”
Section: Regulation Of Secondary Metabolismmentioning
confidence: 99%
“…For example, free terpenoid compounds in grapes impart specific aroma characteristics and vary depending on the grape varietal (Conde et al 2007). Muscat grapes have the highest Figure 3 The predicted pathway leading to the production of the aroma thiols 3-mercaptohexan-1-ol (3-MH) and 3-mercaptohexyl acetate (3-MHA) (adapted from Harsch et al 2013). When the six-carbon (C6) precursors, (E)-trans-2-hexen-1-ol and (E)-trans-2-hexanal have a relative ratio greater than one and a sulfur donor is present, the reaction is driven to produce 3-MH and 3-MHA.…”
Section: Impact Of Starting Materials On Production Of Flavor Componentsmentioning
confidence: 99%
“…Other than release from precursors, the biogenesis of volatile thiols also has been proposed. The direct addition of H 2 S or another sulphur donor to conjugated carbonyl compounds such as (E)-2-hexenal and mesityl oxide, followed by a reduction step, has been shown to contribute significantly to the pool of volatile thiols in Sauvignon blanc wines (Harsch et al, 2013). The formation of the volatile thiols is not fully understood, since the main precursor has yet to be elucidated and the production of these volatile thiols needs further investigation.…”
Section: Volatile Thiolsmentioning
confidence: 99%
“…Practices such as mechanical harvesting, skin contact, pressure during pressing and oxygen exposure could significantly increase the precursor content in the juice and influence the volatile thiol concentration in the corresponding wines (Maggu et al, 2007;Patel et al, 2010;Roland et al, 2010b;Capone & Jeffery, 2011). The liberation of the volatile thiols from the respective precursors depends on conditions such as yeast strain, nitrogen availability and fermentation temperature (Murat et al, 2001a;Masneuf-Pomarède et al, 2006;Swiegers et al, 2006;Subileau et al, 2008b;Anfang et al, 2009;Harsch et al, 2013). More detail regarding the influence of these processes on the volatile thiol concentrations can be obtained from a review article published in 2012 (Coetzee & Du Toit, 2012).…”
Section: Volatile Thiolsmentioning
confidence: 99%
“…S-3-(hexan-1-ol)-L-cysteine (Cys-3MH) (Darriet et al, 1995), as well as glutathionylated S-3-(hexan-1-ol)-glutathione (Coetzee & Du Toit, 2012). Another source of volatile thiols is from the conjugation of (E)-2-hexenal and certain sulphur compounds (Harsch et al, 2013). Research by Tominaga et al (1998) showed that the amplification of varietal aromas during fermentation occurs by the action of yeast carbon-sulphur lyases through an enzymatic mechanism that releases the volatile thiols.…”
Section: Effect Of Skin Contact On the Chemical And Sensory Profile Omentioning
confidence: 99%